Mapping practices in a digital world - Hennig, B (GSDI Association Press, 2016)
Current GIS and mapping techniques are highly technologically driven. With advances in the capabilities especially of online mapping platforms but also advanced geovisualization applications for considerably enhancing digital maps, the map has turned into an advanced digital product that goes far beyond the capabilities of a printed paper map. However, digital mapping practices often remain a mere technical challenge while the wider implications of this digital turn for cartographic practice are less discussed. What is needed is a new approach to rethinking cartographic principles in the digital era.